Diversity of Culturable Bacterial in Various Parts of Luwak’s (Paradoxurus hermaprodithus javanica) Gastrointestinal Tract - SONY SUHANDONO; HERI SETIADI; TATI KRISTIANTI; ALI BUDHI KUSUMA; ANDINI WARIH WEDARINGTYAS; DEMI TRISTAN DJAJADI; I NYOMAN PUGEG ARYANTHA (Microbiology Indonesia, 2016)
Luwak coffee is a highly-priced coffee produced exclusively by the palm civet or luwak (Paradoxurus hermaphrodites ssp.). The purpose of this study was to determine the diversity of culturable bacteria in the gastro intestinal tract of luwak. The bacterial isolates were phenotypically characterized by their morphology and molecularly by analysis of their1,500bp 16s rDNA sequence. The results showed that Enterobacter cloacae and Lactobacillus brevis were found all over luwak’s digestive tract. Enterobacter cloacae was the most common species. The most diverse bacterial population was found in small intestine. Seven bacterial generawere successfully identified from the small intestine and colon, compared to only five genera found in the stomach.